Discourse Markers An Enunciative Approach - Ranger, Graham (Springer International Publishing, 2018)
In our everyday speech we represent events and situations, but we also provide commentary on these representations, situating ourselves and others relative to what we have to say and situating what we say in larger contexts. The present volume examines this activity of discourse marking from an enunciative perspective, providing the first English-language study of the highly influential Theory of Enunciative and Predicative Operations. This semantic/pragmatic theory is popular among academics who specialize in linguistics, discourse analysis, translation studies and didactics in France, but has not yet been widely adopted elsewhere. The tools of this theory are applied to a variety of specific discourse markers in contemporary English and semantic hypotheses are tested using the data-based approach of corpus linguistics. This book therefore provides an English-speaking readership with the keys to understand the theory underlying the author's analysis of a selection of discourse ('anyway', 'indeed', 'in fact', 'yet', 'still', 'like' and 'I think'). This book will provide a valuable resource for students and researchers in linguistics with an interest in discourse markers, natural language argumentation, formal semantics, the interfaces between syntax, semantics and pragmatics, linguistic theorisation and French - or "poststructural" - models of discourse analysis.